CD2 sets quantitative thresholds in T cell activation. - Bachmann, M; Barner, M; Kopf, M (1999)
It has been proposed that CD2, which is highly expressed on T cells, serves to enhance T cell-antigen presenting cell (APC) adhesion and costimulate T cell activation. Here we analyzed the role of CD2 using CD2-deficient mice crossed with transgenic mice expressing a T cell receptor specific for lymphocytic choriomeningitis virus (LCMV)-derived peptide p33. We found that absence of CD2 on T cells shifted the p33-specific dose-response curve in vitro by a factor of 3-10. In comparison, stimulation of T cells in the absence of lymphocyte function-associated antigen (LFA)-1-intercellular adhesion molecule (ICAM)-1 interaction shifted the dose-response curve by a factor of 10, whereas absence of both CD2-CD48 and LFA-1-ICAM-1 interactions shifted the response by a factor of approximately 100. This indicates that CD2 and LFA-1 facilitate T cell activation additively. T cell activation at low antigen density was blocked at its very first steps, as T cell APC conjugate formation, TCR triggering, and Ca(2+) fluxes were affected by the absence of CD2. In vivo, LCMV-specific, CD2-deficient T cells proliferated normally upon infection with live virus but responded in a reduced fashion upon cross-priming. Thus, CD2 sets quantitative thresholds and fine-tunes T cell activation both in vitro and in vivo.